2010
DOI: 10.1002/ejlt.200900066
|View full text |Cite
|
Sign up to set email alerts
|

Betaine supplementation affects the cholesterol but not the lipid profile of pigs

Abstract: This study was undertaken to investigate the effects of long term betaine intake on the cholesterol and lipid profile of Alentejano (AL) pigs. At ,36 kg body weight (BW), castrated male and female pigs fed a commercial (C) diet, were divided into two groups: i) Group C, consuming the C diet; and ii) Group CB, consuming the C diet supplemented with 1 g/kg betaine. Pigs were slaughtered at ,100 kg BW. Fasting plasma concentrations of protein, urea, glucose, TAG, phospholipids, homocysteine, total and LDL-and HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
5
14
1
Order By: Relevance
“…The present study showed that betaine supplementation decreased the concentration of serum cholesterol and HDLC and increased cholesterol level in muscle, which was consistent with the studies by Albuquerque et al [41] and Yang et al [20]. However, Matthews et al [48] and Martins et al [49] reported that betaine supplemented pigs presented higher serum cholesterol. The efficacy of betaine in regulating the concentration of cholesterol in pigs shows variable results and seems to depend on both animal and dietary factors.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that betaine supplementation decreased the concentration of serum cholesterol and HDLC and increased cholesterol level in muscle, which was consistent with the studies by Albuquerque et al [41] and Yang et al [20]. However, Matthews et al [48] and Martins et al [49] reported that betaine supplemented pigs presented higher serum cholesterol. The efficacy of betaine in regulating the concentration of cholesterol in pigs shows variable results and seems to depend on both animal and dietary factors.…”
Section: Discussionsupporting
confidence: 92%
“…Although increased total cholesterol (Matthews et al, 2001;Martins et al, 2010) and decreased HDL/total cholesterol (Martins et al, 2010) have been reported in pigs fed betaine, other authors reported no betaine effect on cholesterol, plasma NEFA or TG (Matthews et al, 1998;Øverland et al, 1999). We found decreased HDL/total cholesterol in betaine pigs, but no significant effects in total cholesterol or fractions.…”
Section: Discussioncontrasting
confidence: 59%
“…Similar results were also reported in finishing pigs (Matthews et al, 1998;Huang et al, 2007) fed betaine. On the contrary, Martins et al (2010) in Alentejano finishing pigs reported no effect of betaine on plasma urea. Matthews et al (1998) suggested that the effects of betaine on protein status of pigs were dependent on the CP and energy content of the diet.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…They found an increase in serum triacylglycerol, indicating that CLA and betaine + CLA could reduce adipose tissue triacylglycerol synthesis from preformed fatty acids, and a decrease in serum growth hormone and serum urea in pigs fed betaine and betaine + CLA diets, suggesting more efficient nitrogen utilization. Likewise, others have found increased plasma triacylglycerol in modern pigs fed CLA or betaine and decreased serum urea in finishing pigs fed betaine . In contrast, Martins et al reported no effect of betaine on plasma urea in Alentejano (Iberian pig raised in Portugal) finishing pigs.…”
Section: Discussionmentioning
confidence: 98%